O direito de apontar o árbitro de parte e a independência deste - Moro, Viviane Tozzi (2022)
One of the features of arbitration, and one of its advantages, is the possibility for the parties to decide on how they will conduct the procedure, choose the number of arbitrators and which arbitrators will judge the dispute, dissociating themselves from the pre-established rules and the slowness of the state judicial system. After the arbitral tribunal formation, the arbitrators have the duty of independence and impartiality throughout the trial. Practice shows, however, that the parties do not always fully rely on the impartiality and independence of the arbitrator who has been appointed by the other party. It may also occur that the arbitrator is tempted to defend the party that has appointed him, mainly by issuing dissenting opinions, which shows that he or she does not agree with all or part of the arbitral award. This tesis analyzes the right of the parties to appoint their arbitrator, as well as the relationship of trust of the parties in the arbitral tribunal and the impartiality and independence of the arbitrators.